STIGMA DAN PROSES SOSIALISASI WARIA SERTA DAMPAKNYA PADA PENINGKATAN RISIKO PENULARAN IMS DAN HIV/AIDS - Husni Abdul Gani; Dewi Rokhmah (Jurnal Ilmu Kesehatan Masyarakat, 2011)
Being a transvestites  is assumed  as deviate behaviour by our society. It is severed with negative stigmatization  as bad    image, dirty, criminal, and having  deviate  sexual orientation, cause this group of people have more risky toward psychological and sexual impact in transmision of STD    and HIV/AIDS. Sosialization proces is needed by transvestitesgeting acceptance in social environment, because transvestites  could not separate from social context. This study aims to analyze the stigmatization  and sosialization process toward transvestites and its impact for the increasing of transmission risk from   STD and HIV/AIDS.It was a qualitative study involved informants aged 25-54  with purposive sampling  in Semarang city. Data  was collected by indepht interview and they’re analyzed by thematic content analysis. The result of this study showed that stigmatization to transvestites was derived from public  society and religius community.  This  rejection  impacts at sosialization    process in family, work place  and society.  Because  our society  assume transvestites identical with deviate behaviour from the norm, and having tranvestites as the family member means ignominy. Consequently they choose as a urbant people.  It cause the increasing of transmission risk on STD and HIV/AIDS.  There are no obstacle in sosialization process with other transvestites  in cebongan. Cebongan is the place they can express themself without rejection from   others. So they can be received as normal individual.  Society is expected accepting  them as a part of their live, with involved them include transvestites with HIV/AIDS in society activity.Key words : Transvestites, stigmatization, sosialization process, STD and HIV/AIDS